2009
DOI: 10.1080/13550280902973952
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 in the central nervous system leads to decreased dopamine in different regions of postmortem human brains

Abstract: Human immunodeficiency virus type 1 (HIV-1) invades the central nervous system (CNS) shortly after infection and becomes localized in varying concentrations in different brain regions, the most vulnerable is the basal ganglia (BG). It is hypothesized that HIV-1-mediated neuropathogenesis involves degeneration of dopaminergic neurons in the substantia nigra and the loss of dopaminergic terminals in the BG, leading to deficits in the central dopaminergic activity, resulting in progressive impairment of neurocogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 83 publications
3
111
0
Order By: Relevance
“…HIV-1 gp41-positive microglia were most numerous in globus pallidus obtained from the brain of AIDS encephalitis patients [27]. Relatively higher levels of HIV-1 RNA were found in dopamine-rich parts of human brain samples (substantia nigra, caudate nucleus, basal ganglia, and globus pallidus) obtained at autopsy [17,28]. Overall, these data suggest that while HIV infection can generally cause brain atrophy, "dopamine-rich" areas can show proportionally more atrophy, suggesting a propensity for HIV in targeting these brain areas.…”
Section: Hiv/aids and Brain Pathology In Dopamine-rich Areasmentioning
confidence: 89%
See 2 more Smart Citations
“…HIV-1 gp41-positive microglia were most numerous in globus pallidus obtained from the brain of AIDS encephalitis patients [27]. Relatively higher levels of HIV-1 RNA were found in dopamine-rich parts of human brain samples (substantia nigra, caudate nucleus, basal ganglia, and globus pallidus) obtained at autopsy [17,28]. Overall, these data suggest that while HIV infection can generally cause brain atrophy, "dopamine-rich" areas can show proportionally more atrophy, suggesting a propensity for HIV in targeting these brain areas.…”
Section: Hiv/aids and Brain Pathology In Dopamine-rich Areasmentioning
confidence: 89%
“…This finding was associated with a loss of nigrostriatal dopaminergic neurons, suggesting a HIV-induced neuronal damage followed by dopamine depletion. In another postmortem sample study, Kumar et al [17] found a significant decrease in dopamine levels in dopamine-rich brain regions, including caudate nucleus, putamen, globus pallidus, and substantia nigra obtained from HIV-1-positive subjects, who actually died of HIV/ AIDS with no opportunistic infection at the time of death, compared to dopamine levels observed in HIV-negative cases. In contrast, in HIV-negative cases, the highest concentration of dopamine was found in dopamine-rich areas, including putamen, caudate, substantia nigra, and the basal ganglia.…”
Section: Hiv/aids and Dopamine Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the caudate nucleus, neurocognitive impairment was correlated with volume reduction and reduced blood flow [35]. Furthermore, virus accumulation together with decreased dopamine levels is present within the caudate nucleus [36,37].…”
Section: Motor Functionmentioning
confidence: 97%
“…Specifically, HIV-induced decreases in caudate/basal ganglia volume Kieburtz et al, 1996) and dopamine levels (Kumar et al, 2009) have been associated with poorer cognitive performance (Hestad et al, 1993;Kieburtz et al, 1996). Similarly, methamphetamine exposure causes neurotoxicity in mesolimbic and mesocortical brain regions (Mark et al, 2004).…”
Section: Introductionmentioning
confidence: 99%